The Tax-adjusted performance metrics: integrating tax planning into risk-adjusted portfolio evaluation - Wiśniewski, Piotr (Journal of Management and Financial Sciences, 2026)
Traditional risk-adjusted performance metrics such as Jensen’s alpha, the Sharpe ratio, and the Information ratio are typically computed on a pre-tax basis, even though taxes materially affect realized investor wealth. This paper develops an implementable framework for tax-adjusted versions of these measures by substituting after-tax returns into standard performance formulas and clarifying the required inputs, assumptions, and interpretation. Using a conceptual – empirical hybrid design, the paper formalizes tax-adjusted alpha, Sharpe, and Information ratios and then benchmarks the magnitude of tax alpha using scenario evidence from six widely used tax-aware portfolio platforms (Vanguard, Morningstar, Parametric, Axioma, Netbasis, and BlackRock). Spanning various tools and representative parameterizations, systematic tax-management techniques – including tax-loss harvesting, gain deferral, and tax-aware rebalancing – produce economically material improvements in after-tax, risk-adjusted performance, with implied annualized tax alpha, typically in the range of 0.7–3.5% for equity direct indexing and 1.0–2.0% for separately managed accounts. The paper concludes with implementation guidance for incorporating tax-adjusted metrics into performance reporting and portfolio analytics, and it discusses practical constraints (transaction costs, wash-sale rules, and investor heterogeneity) that shape realizable benefits.